2006
DOI: 10.1029/2005je002494
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric properties of materials observed by Pancam on the Mars Exploration Rovers: 1. Spirit

Abstract: [1] Multispectral observations of rocks and soils were acquired under varying illumination and viewing geometries in visible/near-infrared wavelengths by the Panoramic Camera (Pancam) on the Spirit Mars Exploration Rover to provide constraints on the physical and mineralogical nature of geologic materials in Gusev Crater. Data sets were acquired at six sites located near the landing site, in the surrounding plains, and in the West Spur and Husband Hill regions of the Columbia Hills. From these $600 images, ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
171
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(183 citation statements)
references
References 55 publications
(131 reference statements)
9
171
2
1
Order By: Relevance
“…Interestingly, a recent laboratory study (Souchon et al, 2011) has shown that natural granular surface samples comprising fresh glass or monocrystals in a high proportion are extremely forward-scattering with narrow scattering lobes. A similar photometric behavior has been previously found for a few ''gray rock'' samples using Pancam in situ data (Johnson et al, 2006), as well as for very glassy lunar regolith simulants (Johnson et al, 2008).…”
Section: Discussionsupporting
confidence: 54%
“…Interestingly, a recent laboratory study (Souchon et al, 2011) has shown that natural granular surface samples comprising fresh glass or monocrystals in a high proportion are extremely forward-scattering with narrow scattering lobes. A similar photometric behavior has been previously found for a few ''gray rock'' samples using Pancam in situ data (Johnson et al, 2006), as well as for very glassy lunar regolith simulants (Johnson et al, 2008).…”
Section: Discussionsupporting
confidence: 54%
“…A number of studies have investigated the photometric roughness of surfaces within the Viking, Pathfinder, and Mars Exploration Rover landing sites (Arvidson et al, 1989;Guinness et al, 1997;Johnson et al, 1999Johnson et al, , 2006aJohnson et al, , 2006b. These studies have shown the martian soils and dusty surfaces have θ -bar values between 4 • and 27 • .…”
Section: Comparison With Photometric and Terrestrial Studiesmentioning
confidence: 98%
“…More recent photometric studies of the surface materials of Mars using telescopic data (e.g., de Vaucouleurs, 1968;O'Leary and Rea, 1968;Binder and Jones, 1972;Thorpe, 1982;de Grenier and Pinet, 1995;Vdovichenko et al, 1997;Bell et al, 1999;Erard, 2000) and spacecraft data (e.g., Guinness, 1981;Arvidson et al, 1989;Johnson et al, 1999Johnson et al, , 2006 have yielded information regarding the photometric properties of the martian surface. For example, O'Leary and Rea (1968) reported a strong opposition surge, which varied inversely with albedo and moderate limb darkening.…”
Section: Introductionmentioning
confidence: 98%